ANALISIS KINERJA PEGAWAI DENGAN PENDEKATAN FENOMENOLOGI UNTUK MENINGKATKAN KUALITAS LAYANAN PASPOR D - Hanif Insan Ma’ruf; Agung Sulistyo Purnomo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Public service is a government obligation carried out by government institutions. Good performance allows public institutions to provide satisfactory services to the community. The Class I Non-TPI Central Jakarta Immigration Office is a government agency located in Central Jakarta which was inaugurated in 1914 which functions to provide maximum public services in the field of immigration and also based on human rights, which are regulated in the Regulation of the Minister of Law and Human Rights Number 2 of 2022 with the aim of providing maximum service quality which is also able to increase public satisfaction. This study uses a qualitative method with an interpretive phenomenological approach. Based on the data analysis that has been carried out, it can be concluded that the performance of employees in the Travel Document Verification Service Section of the Class I Non- TPI Central Jakarta Immigration Office runs according to the Standard Operating Procedures (SOP) that apply in the Class I Non-TPI Central Jakarta Immigration Office. The performance produced by employees is good even though there are still obstacles faced by employees. The inhibiting factors in the Travel Document Verification Service Section of the Class I Non-TPI Central Jakarta Immigration Office are the high workload and frequent disruptions to the service system. Meanwhile, supporting factors are a good working environment, supportive facilities and effective leadership.